login
The OEIS Foundation is supported by donations from users of the OEIS and by a grant from the Simons Foundation.

 

Logo

Please make a donation to keep the OEIS running. We are now in our 56th year. In the past year we added 10000 new sequences and reached almost 9000 citations (which often say "discovered thanks to the OEIS").
Other ways to donate

Hints
(Greetings from The On-Line Encyclopedia of Integer Sequences!)
A118340 Pendular triangle, read by rows, where row n is formed from row n-1 by the recurrence: if n > 2k, T(n,k) = T(n,n-k) + T(n-1,k), else T(n,k) = T(n,n-1-k) + T(n-1,k), for n>=k>0, with T(n,0)=1 and T(n,n)=0^n. 9
1, 1, 0, 1, 1, 0, 1, 2, 1, 0, 1, 3, 4, 1, 0, 1, 4, 9, 5, 1, 0, 1, 5, 15, 20, 6, 1, 0, 1, 6, 22, 48, 28, 7, 1, 0, 1, 7, 30, 85, 113, 37, 8, 1, 0, 1, 8, 39, 132, 282, 169, 47, 9, 1, 0, 1, 9, 49, 190, 519, 688, 237, 58, 10, 1, 0, 1, 10, 60, 260, 837, 1762, 1074, 318, 70, 11, 1, 0 (list; table; graph; refs; listen; history; text; internal format)
OFFSET

0,8

COMMENTS

Definitions. A pendular triangle is a triangle in which row n is generated from the pendular sums of row n-1. Pendular sums of a row are partial sums taken in back-and-forth order, starting with the leftmost term, jumping to the rightmost term, back to the leftmost unused term, then forward to the rightmost unused term, etc.

In each pass, the partial sum is placed in the new row directly under the term most recently used in the sum. Continue in this way until all the terms of the prior row have been used and then complete the new row by appending a zero at the end. Pendular sums are so named because the process resembles a swinging pendulum that slows down on each pass until it eventually comes to rest in the center.

In the simplest case, pendular triangles obey the recurrence: if n > 2k, T(n,k) = T(n,n-k) + T(n-1,k), else T(n,k) = T(n,n-1-k) + p*T(n-1,k), for n>=k>0, with T(n,0)=1 and T(n,n)=0^n, for some fixed number p.

In which case the g.f. G=G(x) of the central terms satisfies: G = 1 - p*x*G + p*x*G^2 + x*G^3.

More generally, a pendular triangle is defined by the recurrence: if n > 2k, T(n,k) = T(n,n-k) + T(n-1,k), else T(n,k) = T(n,n-1-k) + Sum_{j>=1} p(j)*T(n-1,k-1+j), for n>=k>0, with T(n,0)=1 and T(n,n)=0^n.

Remarkably, the g.f. G=G(x) of the central terms satisfies: G = 1 + x*G^3 + Sum_{j>=1} p(j)*x^j*[G^(2*j) - G^(2*j-1)].

Further, the g.f. of the m-th lower semi-diagonal equals G(x)^(m+1) for m>=0, where the m-th semi-diagonal consists of those terms located at m rows below the central terms.

For variants of pendular triangles, the main diagonal may be nonzero, but then the g.f.s of the semi-diagonals are more complex.

LINKS

Paul D. Hanna, Rows n = 0..20, flattened.

FORMULA

T(2*n+m,n) = [A108447^(m+1)](n), i.e., the m-th lower semi-diagonal forms the self-convolution (m+1)-power of A108447; compare semi-diagonals to the diagonals of convolution triangle A118343.

EXAMPLE

Row 6 equals the pendular sums of row 5:

[1, 4, 9, 5, 1, 0], where the sums proceed as follows:

[1,__,__,__,__,__], T(6,0) = T(5,0) = 1;

[1,__,__,__,__, 1], T(6,5) = T(6,0) + T(5,5) = 1 + 0 = 1;

[1, 5,__,__,__, 1], T(6,1) = T(6,5) + T(5,1) = 1 + 4 = 5;

[1, 5,__,__, 6, 1], T(6,4) = T(6,1) + T(5,4) = 5 + 1 = 6;

[1, 5,15,__, 6, 1], T(6,2) = T(6,4) + T(5,2) = 6 + 9 = 15;

[1, 5,15,20, 6, 1], T(6,3) = T(6,2) + T(5,3) = 15 + 5 = 20;

[1, 5,15,20, 6, 1, 0] finally, append a zero to obtain row 6.

Triangle begins:

1;

1, 0;

1, 1, 0;

1, 2, 1, 0;

1, 3, 4, 1, 0;

1, 4, 9, 5, 1, 0;

1, 5, 15, 20, 6, 1, 0;

1, 6, 22, 48, 28, 7, 1, 0;

1, 7, 30, 85, 113, 37, 8, 1, 0;

1, 8, 39, 132, 282, 169, 47, 9, 1, 0;

1, 9, 49, 190, 519, 688, 237, 58, 10, 1, 0;

1, 10, 60, 260, 837, 1762, 1074, 318, 70, 11, 1, 0;

1, 11, 72, 343, 1250, 3330, 4404, 1568, 413, 83, 12, 1, 0; ...

Central terms are T(2*n,n) = A108447(n);

semi-diagonals form successive self-convolutions of the central terms:

T(2*n+1,n) = A118341(n) = [A108447^2](n),

T(2*n+2,n) = A118342(n) = [A108447^3](n).

PROG

(PARI) {T(n, k) = if(n<k || k<0, 0, if(k==0, 1, if(n==k, 0, if(n>2*k, T(n-1, k) + T(n, n-k), T(n-1, k) + T(n, n-1-k)))))}

for(n=0, 12, for(k=0, n, print1(T(n, k), ", ")); print(""))

CROSSREFS

Cf. A108447 (central terms), A118341, A118343; variants: A118344 (Catalan), A118362 (ternary), A118350, A118355.

Sequence in context: A286932 A259475 A323224 * A213276 A210391 A071921

Adjacent sequences:  A118337 A118338 A118339 * A118341 A118342 A118343

KEYWORD

nonn,tabl

AUTHOR

Paul D. Hanna, Apr 25 2006

STATUS

approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recent
The OEIS Community | Maintained by The OEIS Foundation Inc.

License Agreements, Terms of Use, Privacy Policy. .

Last modified December 2 07:22 EST 2020. Contains 338868 sequences. (Running on oeis4.)